Features and geomorphic response of mountainous river by reach scale - Haron, Nor Azidawati; Yusuf, Badronnisa; Nurhidayu, Siti; Sulaiman, Mohd Sofiyan; Ab Razak, Mohd Shahrizal (Springer Singapore, 2021)
Many activities such as hard engineering control measures have made the river out of natural rivers. The loss of physical and biological function in altered river have induced large scale adverse response by the public throughout Malaysia. Therefore, an understanding of river’s equilibrium characteristics is important for managing the quality of river in mountainous catchment area. The aim of this study is to investigate the features and geomorphic response of mountainous river. The method of data collection is by extensive fieldwork including measuring the river geometry, hydraulics properties, sediment load characteristics, and size of bed materials at reach scale. This research is significant for managing the quality of water resources in Malaysia where most of it is located at mountainous area. The criteria presented by morphology and the geomorphic response that occurs along the river reach has proven that the river is in equilibrium condition.